Tan27518
Rozwiązane

Ile liczb całkowitych jest rozwiązaniem równania (x-2)^2(x^2-9)(2x^2-5x+3)=0



Odpowiedź :

Cześć!

Obliczenia

[tex](x-2)^2(x^2-9)(2x^2-5x+3)=0\\\\\\(x-2)^2=0\\x-2=0\\x=2\in\text{C}\\\\\\x^2-9=0\\(x+3)(x-3)=0\\x+3=0\longrightarrow x=-3\in\text{C}\\x-3=0\longrightarrow x=3\in\text{C}\\\\\\2x^2-5x+3=0\\a=2, \ b=-5, \ c=3\\\Delta=b^2-4ac\rightarrow(-5)^2-4\cdot2\cdot3=25-24=1\\\sqrt{\Delta}=\sqrt1=1\\x_1=\frac{-b-\sqrt{\Delta}}{2a}=\frac{-(-5)-1}{2\cdot2}=\frac{5-1}{4}=\frac{4}{4}=1\in\text{C}\\x_2=\frac{-b+\sqrt{\Delta}}{2a}=\frac{-(-5)+1}{2\cdot2}=\frac{5+1}{4}=\frac{6}{4}=1,5\notin\text{C}[/tex]

Odp. Równanie jest spełnione przez cztery liczby całkowite.